Safety and efficacy of health supplement (Stevia rebaudiana) - Mazlina Mukhtar; Chua Say Tiong; Sarah I Bukhari; Amir Heberd Abdullah; Long Chiau Ming (Archives of Global Professionals, 2016)
Purpose: The aim of this review is to evaluate the safety and efficacy of a product containing Stevia rebaudiana and its related marketing restriction governed by laws. Methods: An electronic search was conducted through searching at Cochrane Library, EMBASE, PUBMED to assess the literature of Stevia rebaudiana. Results: Stevia was considered safe to be used as sugar substitution in patients with diabetes. No serious adverse events and health risk were reported. However, until now, most of the beneficial results were from the study conducted in short-term. Not many studies conducted to assess the health risk of consuming stevia for long-term effect. Therefore, consumers must be warned to used stevia product cautiously and not exceed the recommended dose as instructed. No definite findings yet regarding dose range, minimum and maximum, to achieve optimal outcome and avoid risk of hypoglycemia. Conclusion: Although some countries still banned the use of stevia since lack of toxicology profile, it was credited with the various health benefits. The Joint Expert Committee on Food Additives revealed that stevia extracts containing 95% steviol glycosides are safe for human use in the range of 4 mg/kg of body weight/day.